Seafood consumption pattern and its relationship with blood arsenic, blood lead and genetic polymorphism of GST genes among the coastal community of Melaka, Malaysia - Mohd Noor, Farrah Atiqah (2018)
Heavy metals such as arsenic (As) and lead (Pb) exposure through the consumption of seafood are an environmental issue of concern. Biomonitoring of whole blood heavy metals level gave an insight of the total internal body burden due to the exposure of heavy metals. The level of heavy metals of an individual are interrelated with the frequency of seafood intake and genetic variants of glutathione S-tranferases (GST). The objectives of this study were to determine the association between blood As and Pb concentration and socio-demographic background, potential sources of exposure and polymorphic variants of GST genes. This was a cross-sectional study conducted from September 2014 until February 2016 among 403 subjects with age ranging between 18 to 60 years old. Further blood analysis were voluntarily participated by 63 respondents. The socio-demographic information, seafood frequency intake and other potential exposures to heavy metals were obtained through pre-tested questionnaire. Heavy metals concentration in blood were determined by inductively coupled plasma- mass spectrometry (ICP-MS), polymorphic variants of GSTM1 and GSTT1 were analyzed by multiplex polymerase chain reaction (PCR) while polymorphic variants of GSTP1 were analyzed by polymerase chain reaction- restriction fragment length polymorphism (PCR-RFLP). Majority of the respondents in Melaka were a frequent eater of fish (≥ 3 times per week) with percentage of 92.1% (n=403). The median blood arsenic (BAs) concentration of respondents was 0.076 μg/L (interquartile range: 0.048 μg/L) which range between 0.01 to 0.36 μg/L and the median blood lead (BPb) concentration of respondents was 1.204 μg/L (interquartile range: 1.424 μg/L) which range between 0.06 to 5.06 μg/L respectively (n=63). Expected prevalence of genetic polymorphism in GSTM1 and GSTT1 of the respondents of 63.5% and 31.8% respectively (n=63) were observed. The number of respondents who have both deleted genes for GSTM1 and GSTT1 was 15 (23.8%). The frequency of genetic polymorphism in GSTP1 was 55.6%, in which 29 (46.0%) of the respondents were having the heterozygous (Ile/Val) polymorphism while the other 6 (9.6%) respondents were having the homozygous mutant (Val/Val). A significant association was observed between seafood-based product frequency intake and BPb concentration (p < 0.05). Age, duration of settlement, household income, gender, educational level and BMI did not significantly associated with the BAs and BPb concentration of respondents. There were no significant relationship between seafood frequency intake, smoking and occupational exposure of study subjects with BAs and BPb concentration. The polymorphic GST variants were also found not significantly correlated to heavy metals concentrations.